Using of MATLAB Statistics Toolbox for Data Analysis in Social Sciences with Chat GPT-3 prompts - Şengür, Dönüş (My University, 2023)
This paper explores the potential usage of ChatGPT-3, a powerful language model developed by OpenAI, within the MATLAB Statistical Toolbox (ST) for social science research. ChatGPT-3 is a highly advanced model that has shown remarkable performance in a wide range of natural language processing tasks. However, its usage in social science research is still relatively new and has not been widely explored. The main advantage of using ChatGPT-3 in social science research is its ability to process large amounts of unstructured text data, which is becoming increasingly prevalent in social science research. However, there are also some potential disadvantages to using ChatGPT-3, such as its complexity, lack of interpretability, and proprietary nature. This paper aims to provide an overview of the current state of ChatGPT-3 usage in social science research and to discuss the potential advantages and disadvantages of using this model within MATLAB ST. This paper, it is aimed to show how ChatGPT-3 can assist social science researchers in MATLAB ST in the processing of their datasets. Because data analysis can be challenging for social science researchers for several reasons as social science data can often be complex, with multiple variables and multiple levels of analysis. This can make it difficult to analyze and interpret the data in a meaningful way. Therefore, some sample hints, where ChatGPT-3 prompts are used to handle such statistical operations in MATLAB ST, are provided. The comments that ChatGPT-3 gives out are analyzed. It is believed that ChatGPT-3 will be a good assistant for social science researchers in MATLAB ST.
Keywords: Data analysis; Artificial intelligence; ChatGPT-3; MATLAB ST in social science